MERANCANG TEATER IMERSIF DENGAN KONSEP MEMBAYANGKAN-KEMBALI CERITA KAWASAN ANCOL - Andree Andree; Alvin Hadiwono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The development of technology is a global phenomenon that has a major impact on changes in human lifestyles and mindsets. The next generation of Alpha is a generation born in an era of rapid technological development. Entertainment, communication, education, to everyday life revolve around technology. Facing this change, the architecture also needs to adapt. Meanwhile, the urban spatial structure that has been formed is often not prepared to adapt to this rapid technological development. The Ancol area, which is known as the largest entertainment area in Jakarta, is also affected by this global phenomenon. The point that was once crowded as a main destination for recreation and entertainment has experienced a reduction in human movement in it. The reduced movement of people inside has resulted in several buildings undergoing a change in function in an effort to re-attract people to the Ancol area. The degraded point is used as an inappropriate expression container. Through the research that has been done, architecture can take advantage of technology as an effort to adapt. Rapid technological developments allow architecture to re-imagine the entertainment of the Ancol area. Through analysis, the addition of an immersive theater program at the problematic point can meet the needs of entertainment that can accommodate regional expressions. As a result, architecture can revive an entertainment area that has decreased due to changing entertainment needs through urban acupuncture. Keywords:  Ancol District;, Entertainment; Immersive Theatre; Re-Imagining; Urban Acupuncture Abstrak Perkembangan teknologi merupakan salah satu fenomena global yang memiliki dampak besar terhadap perubahan gaya hidup dan pola pikir manusia. Generasi Alpha yang mendatang merupakan generasi yang dilahirkan di era perkembangan teknologi yang pesat. Hiburan, komunikasi, edukasi , hingga kehidupan sehari-hari berputar sekitar teknologi. Menghadapi perubahan ini, arsitektur juga perlu beradaptasi. Sementara itu, struktur ruang kota yang sudah terbentuk kerap belum dipersiapkan untuk beradaptasi dengan perkembangan teknologi yang pesat ini. Kawasan Ancol yang dikenal sebagai kawasan hiburan terbesar di Jakarta ikut terdampak oleh fenomena global ini. Titik yang tadinya ramai dikunjungi sebagai tujuan utama rekreasi dan hiburan mengalami pengurangan pergerakan manusia didalamnya. Berkurangnya pergerakkan manusia didalamnya mengakibatkan beberapa bangunan mengalami perubahan fungsi sebagai upaya untuk kembali menarik orang menuju kawasan Ancol. Titik yang mengalami degradasi dijadikan wadah ekspresi yang kurang tepat. Melalui riset yang telah dilakukan, arsitektur dapat memanfaatkan teknologi sebagai upaya untuk beradaptasi. Perkembangan teknologi yang pesat memungkinkan arsitektur untuk membayangkan-kembali hiburan pada  kawasan Ancol. Melalui analisis, adanya penambahan program teater imersif pada titik yang bermasalah dapat memenuhi kebutuhan hiburan yang dapat mewadahi ekspresi kawasan. Dampaknya, arsitektur dapat membangkitkan kawasan hiburan yang mengalami penurunan akibat perubahan kebutuhan hiburan melalui urban akupunktur.